Influence of Halal Awareness, Islamic Branding, Celebrity Endorsers and Israel Product Boicots on E-Commerce Product Purchase Decisions (Study of Lecturers and Staff of Sulthan Thaha Saifuddin Jambi State Islamic University) - Assiddiqi, M. Irfan; AA Miftah; Safitri, Yuliana; Rahma, Sri; Ramadhan, Argianov; Kharisma, Anya Suci; Sanjaya, Aldi (PT Inovasi Pratama Internasional, 2024)
This research aims to determine the influence of Halal Awareness, Islamic Branding, Celebrity Endorser, and Boycott of Israeli Products on product purchasing decisions in e-commerce by UIN STS Jambi Lecturers and Staff. The population used in this research was UIN STS Jambi Lecturers and Staff, totaling 901 people. The sampling technique in this research was Probability Sampling technique using the Krejcie and Morgan counting technique with a total sample or respondents of 160 people. The method used in this research is a quantitative method with primary data, namely distributing questionnaires and observations. In calculating and analyzing data, researchers utilized the SemPLS 4.0 program . The results of this research show that Halal Awareness has a positive and significant effect on purchasing decisions because of the high halal awareness of respondents. Islamic Branding has a positive and significant effect on purchasing decisions because it can influence the image and credibility of the product. Celebrity Endroser has a positive and significant effect on purchasing decisions because it can increase the attractiveness of the product. Boycotting Israeli products has a negative and insignificant effect on product purchasing decisions because with a boycott of Israeli products consumers will be more careful. The hope is that producers can improve the Islamic and halal aspects of their products, as well as make maximum use of the presence of celebrity endorsers and always maintain a good image of the product.